New ways of working and psychological well-being: Work intensity as a target variable of job resources - Soucek, Roman; Voss, Amanda Sophie; Drexler, Hans; Moser, Klaus (International Journal of Workplace Health Management, 2024)
Purpose Digitalization and flexibility of workplaces as aspects of new ways of working are associated both positively and negatively with employees’ well-being. However, the mechanisms behind this relationship are not clear yet. We present work intensity as a link between new ways of working and psychological well-being. Furthermore, we address two job resources to alter this association: autonomy and boundary control. Design/methodology/approach Overall, 1,099 employees of a public administration organization participated in the survey and answered a web-based questionnaire. The organization was in the transition to new ways of working including the introduction of a digital filing system and remote work. Findings The results of regression analyses provided evidence that flexibility and dissolution of boundaries were positively related to work intensity, which in turn was associated with emotional exhaustion and work engagement. Thus, new ways of working were negatively associated with psychological well-being, mediated by work intensity. Further analyses revealed that the job resources of autonomy and boundary control moderated the relationship between flexibility respectively dissolution of boundaries with work intensity. Thus, these job resources acted as buffering factors and mitigated the association of new ways of working with work intensity. Originality/value The results indicated that work intensity could be perceived as a conceptual bridge between new ways of working and psychological well-being providing a promising target variable for the deployment of job resources to preserve employees’ well-being.
Keywords: work intensity; boundary control; new ways of working